2016
DOI: 10.1177/1359105315581069
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study comparing psychological profiles and its congruence with clinical performance among patients with functional or motility digestive disorders

Abstract: Functional gastrointestinal disorders (FGDs) have been related with different psychological conditions. On the contrary the role of psychological factors within gastrointestinal motor disorders (GMDs) remains unclear. The objective of this study was to explore the differences and congruence with clinical performance of the psychological profile and subjective functionality among patients diagnosed with FGDs and GMDs. Using a double-blind design, fifty-six inpatients from a Gastroenterology Department were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…For instance, according to previous literature, gastroenterologists tend to misattribute FGDs diagnoses among patients with psychological distress [22]. Relatedly, our study group has shown in previous studies how the perception of functionality is different among clinicians and patients with FGDs, but congruent in patients with GMDs [23]. In a similar way, some studies in patients with asthma have shown incongruences between self-reported and clinician-reported measures [24].…”
Section: Introductionsupporting
confidence: 75%
“…For instance, according to previous literature, gastroenterologists tend to misattribute FGDs diagnoses among patients with psychological distress [22]. Relatedly, our study group has shown in previous studies how the perception of functionality is different among clinicians and patients with FGDs, but congruent in patients with GMDs [23]. In a similar way, some studies in patients with asthma have shown incongruences between self-reported and clinician-reported measures [24].…”
Section: Introductionsupporting
confidence: 75%
“…In a previous exploratory study we observed no relevant differences in psychopathology, personality and functioning between inpatients diagnosed with gastrointestinal motor disorders (GMDs) or functional gastrointestinal disorders (FGDs) [1]. However, we observed higher levels of incongruence between clinician-assessed performance status and patients' self-reported levels of functioning among patients diagnosed with FGDs.…”
Section: Tablementioning
confidence: 43%
“…As in our pilot study [1], differences between GMDs and FGDs in SCL-90-R scores, duration of illness and BMI did not yield statistically significant differences. However, we found a statistically significant difference in KPS scores (GMDs: 66 ± 18 vs. FGDs: 75 ± 13; t = 2.9, p < 0.005).…”
Section: Tablementioning
confidence: 55%
“…Only few studies investigating the effects of alexithymia on treatment outcomes and symptom severity with a longitudinal design (Porcelli et al, 2003 , 2007a , 2017 ). All the other studies included in this review (Porcelli et al, 2004 , 2014b ; Jones et al, 2006 , 2013 ; van Kerkhoven et al, 2006 ; Farinelli et al, 2007 ; Van Oudenhove et al, 2011b ; Phillips et al, 2013 ; Eiroa-Orosa et al, 2015 ; Dibaise et al, 2016 ) were cross-sectional. Moreover, all but two studies (Jones et al, 2006 ; Phillips et al, 2013 ) did not include control samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no significant TAS-20 difference was found by Jones et al ( 2006 ) between 74 IBS (42 ± 12) and 48 IBD patients (43 ± 12), even though they were more alexithymic than 55 healthy subjects (38 ± 9) ( p = 0.005). Same results were reported by other two studies comparing TAS-20 mean scores between 151 FD (47.62 ± 13.06) and 58 non-FD patients (45.62 ± 13.32) (Cohen's d = 0.14; p = 0.332) (Dibaise et al, 2016 ), and between 28 patients with FGID (46.16 ± 13.91) and 17 patients reporting GI motility disorders (48.43 ± 17.15) ( z = −0.63; p = 0.527) (Eiroa-Orosa et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%